1995
DOI: 10.1002/pros.2990260204
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic activity and prognosis in prostatic adenocarcinoma

Abstract: Mitotic figures were quantitated by two different methods (number of mitotic figures in 10 high power fields, MI; number of mitotic figures/mm2 of neoplastic epithelium, M/V) in a series of 303 prostatic adenocarcinomas, and the results were related to clinical and histological features as well as to prognosis. Gleason score and mitotic indices were significantly interrelated. Invasive T3-4 tumors showed higher mitosis counts than did the local ones, and metastasis at the time of diagnosis was related to mitot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…The perineural growth was categorized into two groups; present or absent. The mitotic figures were identified and calculated from the most actively proliferating area in the section (Vesalainen et al, 1995). The volume corrected mitotic index method (M/V index) was used, which expresses the number of mitotic figures/square millimetre of tumour tissue in the section (Vesalainen et al, 1995).…”
Section: Histological Methods and Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The perineural growth was categorized into two groups; present or absent. The mitotic figures were identified and calculated from the most actively proliferating area in the section (Vesalainen et al, 1995). The volume corrected mitotic index method (M/V index) was used, which expresses the number of mitotic figures/square millimetre of tumour tissue in the section (Vesalainen et al, 1995).…”
Section: Histological Methods and Flow Cytometrymentioning
confidence: 99%
“…The mitotic figures were identified and calculated from the most actively proliferating area in the section (Vesalainen et al, 1995). The volume corrected mitotic index method (M/V index) was used, which expresses the number of mitotic figures/square millimetre of tumour tissue in the section (Vesalainen et al, 1995). The results of flow cytometry have been reported in detail previously (Vesalainen et al, 1994).…”
Section: Histological Methods and Flow Cytometrymentioning
confidence: 99%
“…The mitotic figures were identified and calculated from the most actively proliferating area in the section [3]. The volume–corrected mitotic index method (M/V index) was used, which expresses the number of mitotic figures/mm 2 of tumour tissue in the section [3]. …”
Section: Methodsmentioning
confidence: 99%
“…The earlier studies have revealed that cell proliferation indices and factors related to cell adhesion are important prognostic factors in PC [1, 2, 3]. …”
Section: Introductionmentioning
confidence: 99%
“…We were specially interested in examining the prognostic value of mitotic indices in gastric cancer because of their powerful prognostic significance in several other human malignancies (Haapasalo et al, 1989;Lipponen et al, 1990;Aaltomaa et al, 1992;Vesalainen et al, 1995).…”
mentioning
confidence: 99%